Efficacy of adjunctive photodynamic therapy in the treatment of generalized aggressive periodontitis: A randomized controlled clinical trial - KURU, LEYLA (WILEY, 2019)
Objectives Generalized aggressive periodontitis (GAgP) is a distinct type of periodontal disease characterized by rapid loss of attachment and alveolar bone occurring in young individuals. Photodynamic therapy (PDT) was introduced in periodontology as an adjunctive approach to non-surgical periodontal treatment (NPT) in periodontitis patients. In this trial, the aim was to evaluate the clinical and microbiological effects of adjunctive PDT to NPT in patients with GAgP. Methods In this prospective controlled clinical study, 24 systemically healthy, non-smoking subjects with GAgP were enrolled. Subjects were randomly assigned into a control group (n = 12) treated with NPT only or to a test group (n = 12) treated with NPT and PDT. Plaque index, sulcus bleeding index (SBI), probing depth (PD), relative attachment level, gingival recession, and tooth mobility were recorded at baseline and on day 63. Microbiological samples were obtained from the sites with PD >= 5 mm at both time periods and evaluated for Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, and Treponema denticola via micro-IDent (R) test. Results Clinical and microbial parameters declined significantly in both groups after the treatments (P < 0.01). The comparisons between the groups showed that only the full mouth SBI score of the test group was significantly lower than the control group on day 63 (P < 0.05). Although the reduction in periodontopathogens of the test group was greater than the control group, there was no significant difference between the groups (P > 0.05). Conclusions Within the limits of this study, it can be concluded that in the treatment of GAgP, usage of PDT as an adjunct to NPT does not lead to any beneficial effects on the investigated clinical and microbiological parameters except for SBI. Nevertheless, the statistically significant difference for the SBI score demonstrates that PDT may have additional effect on the reduction in gingival bleeding. Lasers Surg. Med. 51:167-175, 2019. (c) 2018 Wiley Periodicals, Inc.
Keywords: aggressive periodontitis; dental plaque; periodontal debridement; photochemotherapy; PORPHYROMONAS-GINGIVALIS; LETHAL PHOTOSENSITIZATION; ACTINOBACILLUS-ACTINOMYCETEMCOMITANS; NONSURGICAL TREATMENT; SUBGINGIVAL PLAQUE; BACTERIA; BLUE; AMOXICILLIN/METRONIDAZOLE; PARAMETERS; PATHOGENS